FACTORS AFFECTING CUSTOMERS’ SELECTION OF ENVIRONMENTAL FRIENDLY PACKAGING - Ruengkrit, Suparada; Laohavichien, Tipparat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objective of this quantitative study is to compare the consumers’ selection choice of environmentally friendly packaging in terms of packaging design and brand trust classified by demographic characteristics of consumers. In this study, the packaging design was examined in two aspects: structure and graphics. The questionnaire was used to collect data from 400 respondents. Statistical analyses presented are frequency, percentage, mean, standard deviation, and one-way analysis of variance. Results showed that consumers rate a higher level of importance to brand trust than packaging design. Packaging design in terms of graphics was considered more important than structure. In addition, a consumer with a higher level of education and more experience in using environmentally friendly products is more concerned with the packaging design structure than its graphics. Also, a consumer with different average monthly incomes showed significant differences in their selection of environmentally friendly packaging regarding the product’s brand trust at the 0.05 level of statistical significance. Based on this research, the recommendations are that packaging manufacturers should focus on packaging’s appropriate size and weight. The main characteristics of excellent packaging viewed by consumers are as follows: convenience to use, durability, well protected of the product from damage, and keeping the product in good condition. Moreover, packaging manufacturers should offer consumers various packaging types to support consumers with different levels of income and educational backgrounds.